Effectivity of Musa paradisiaca extract to control Saprolegnia sp. infection on giant gourami larvae - Nuryati, Sri; Aulia, Nadia; Rahman, , (Indonesian Society of Scientific Aquaculture (ISSA), 2015)
ABSTRACT Larval stage of giant gourami is a critical period due to fungal infection, such as Saprolegnia sp. infection. There are some plants which have antiseptic compound like banana Musa paradisiaca. This research was aimed to examine the effectiveness of the banana stem extract M. paradisiaca to control Saprolegnia sp. infection on giant gurami larvae through immersion. Eight-day old gorami larvae (at the initial of 0.5±0.03 cm) was reared in an aquarium sized 25×25×25 cm3 at the density of 8 fry/L. Culture media were added banana stem extract at the dose of 0; 0.08; 0.12; and 0.16 g/L during 21 days of rearing period. Challenge test was performed for 14 days by giving Saprolegnia sp. spores at the density of 104 cells/mL and banana stem extract. The treatment dose of 0.16 g/L has showen survival 100% than positive control after the challenge test. Keywords: giant gourami, Musa paradisiaca, Saprolegnia sp., fry ABSTRAK Fase larva ikan gurami merupakan masa kritis terhadap infeksi cendawan, seperti jenis Saprolegnia sp. Beberapa tanaman memiliki daya antiseptik seperti tanaman pisang ambon Musa paradisiaca. Penelitian ini bertujuan untuk menguji efektivitas ekstrak batang pisang ambon M. paradisiaca dalam mengurangi infeksi Saprolegnia sp. pada larva ikan gurami melalui media pemeliharaan. Larva gurami umur delapan hari (panjang larva 0,5+0,03 cm) dipelihara pada akuarium berukuran 25×25×25 cm3 dengan padat tebar 8 ekor/L. Media pemeliharaan diberi ekstrak batang pisang ambon dosis 0; 0,08; 0,12; dan 0,16 g/L selama 21 hari. Uji tantang dilakukan selama 14 hari dengan pemberian spora Saprolegnia sp. kepadatan 104 sel/mL dan ekstrak batang pisang ambon. Perlakuan dosis 0,16 g/L memberikan kelangsungan hidup sebesar 100% yang lebih tinggi dibandingkan perlakuan kontrol positif setelah uji tantang. Kata kunci: giant gourami, Musa paradisiaca, Saprolegnia sp., larva